Inobservancia del principio de la prohibición de autoincriminación en la infracción deingesta de alcohol y sustancias sujetas a fiscalización, por negarse el conductor a la práctica delos exámenes - Vicente Cumbicos, Nataly Silvana (2023)
In the following work, entitled: "Non-observance of the prohibition on self-incrimination in the infraction of alcohol and controlled substances intake, as the driver refused to take the test", it has been presented a critical legal analysis of the violation of the driver's right to defense when they refuse to take a test to verify their state of intoxication or drunkenness, allowing the criminal procedural rule of Art. 464 numeral 5 of the Organic Integral Penal Code allows that in case the driver refuses to be examined, it will be presumed that he/she is in the maximum degree of drunkenness or intoxication due to the effect of alcohol and substances subject to control. Likewise, the psychosomatic tests that the traffic agents perform in the field, recorded by audiovisual means, will be valid; although the National Court of Justice has considered that the right to prohibition of self-incrimination should be understood as the refusal to take an examination or to abstain from giving evidence that may lead to criminal liability against him. The Curricular Integration Work is framed within a quantitative methodology. Interviews and surveys have been taken as instruments, which have been applied to different legal professionals. A positive outcome will be generated as a proposal for the following work on curricular integration after adhering to the foundations, paradigms, methodology and the order of research. With the necessary criticality, foundations and knowledge, the need to modify the penal legal norm that allows the presumption of the driver's refusal to take a road test is determined. Key words: Prohibition of self-incrimination, right to defense, refusal of examination, drunkenness, narcotic substances